Kepemimpinan Dan Motivasi Berpengaruh Terhadap Kinerja Dengan Moderating Disiplin Kerja Guru Pada Tk Sweet Butterfly Montessori Tangerang - Erna Kristuti; Zaharuddin Zaharuddin; Suhardi Suhardi (Journal of Innovative and Creativity, 2025)
This study aims to examine the influence of leadership and motivation on teacher performance with work discipline as a moderating variable at TK Sweet Butterfly Montessori Tangerang. The research employed a quantitative approach with an associative-correlational design. Data were collected through questionnaires distributed to 30 teacher respondents. The results show that, partially, leadership has a positive and significant influence on teachers’ work discipline, and motivation also has a positive and significant influence on work discipline. Simultaneously, leadership and motivation have a positive and significant influence on work discipline. In addition, leadership and motivation simultaneously have a positive and significant effect on teacher performance. The moderating model of work discipline in mediating the influence of leadership and motivation on teacher performance could not be analysed using SPSS 24. Nevertheless, multicollinearity tests showed valid results, and all variable indicators were declared valid with correlation coefficients (r-count) greater than the critical value (r-table = 0.361) at the 5% significance level. The reliability test using Cronbach’s Alpha produced values greater than 0.700, indicating that the research instrument is reliable. The normality test using the Kolmogorov-Smirnov method indicated that the data are normally distributed (Asymp. Sig = 0.200 > 0.05). The hypothesis testing using the F-test revealed that leadership, motivation, and work discipline simultaneously have a significant effect on teacher performance (significance = 0.000). However, based on the t-test, it was found that leadership does not have a significant effect on teacher performance, while motivation and work discipline have a positive and significant influence on teacher performance.